Genetic Structuralism Analysis in “Go Set A Watchman” by Harper Lee - Atmana, Bima; Sumitro, Sumitro (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The purpose of this study is to create a literature sociological analysis of the novel Go Set a Watchman. This study aims to reveal the worldview of the author by using Genetic Structuralism theory. The focus of the research is as follows; 1) Analyzing the literary structure of the novel 2) The social background of Harper Lee in relation with the novel 3) The historical events and condition of the society 4) The author’s world view in the novel. The result of the analysis shows that Harper Lee sees the conditions of the society, at the time the novel was written.